Imaging endocervical mucus anatomy and dynamics in macaque female reproductive track using optical coherence tomography - Chen, Siyu; Yi, Ji; Dong, Biqin; Sun, Cheng; Kiser, Patrick F.; Hope, Thomas J.; Zhang, Hao F. (Quantitative Imaging in Medicine and Surgery, 2014)
Background: Endocervical mucus acts as an important barrier to block human immunodeficiency virus (HIV) infection and other sexually transmitted diseases (STDs). Disruption of the mucus layer increases the risk of infection for females. An effective method to image the mucus properties can serve as a pre-screening step to risk-stratify the susceptible population. Methods: We proposed to use optical coherence tomography (OCT) to quantitatively measure the thickness of endocervical mucus. We used a home-built bench-top OCT system to monitor the dynamic change in mucus thickness of a cultivated sample. We also fabricated a prototype endoscopic OCT probe to demonstrate potential in situ applications. Results: We observed a 200% increase in the endocervical mucus thickness after cultivating in 37 °C phosphate buffered saline solution for 30 minutes. During mucus hydrolysis, we found that mucus layer thickness decreased to about 60% of its original value after applying neuraminidase. Three dimensional volumetric image of intact macaque inner vaginal wall was also acquired. Conclusions: We demonstrated that OCT can quantitatively measure the endocervical mucus thickness and its dynamics in ex vivo experiments. Endoscopic OCT has the potential to resolve fine structures inside macaque female reproductive track (FRT) for in vivo applications.